Penguatan Pengaturan Corporate Social Responsibility terhadap Perusahaan Platform Digital dalam Mendukung Perlindungan dan Pemberdayaan UMKM Digital di Indonesia - Alviani Maulida; Surahman Surahman (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The rapid growth of the digital economy has positioned digital platform companies as key actors influencing the sustainability of Micro, Small, and Medium Enterprises (MSMEs). However, Indonesia's Corporate Social Responsibility (CSR) framework remains limited to companies operating in or related to natural resources, making it insufficient to address the characteristics of the digital economy. This article analyzes the regulation of CSR for digital platform companies and proposes a regulatory strengthening model to enhance the protection and empowerment of MSMEs. This normative legal research employs statutory, conceptual, and comparative approaches. The findings reveal that the existing CSR framework still adopts a sector-based approach, which is no longer aligned with the development of digital platforms and MSME protection. Therefore, regulatory reform should adopt an impact-based approach, expand the scope of obligated legal subjects, adjust CSR implementation to the characteristics of digital platforms, and strengthen supervisory mechanisms to promote a fair and sustainable digital economy.